Exploring the Control in Antibacterial Activity of Silver Triangular Nanoplates by Surface Coating Modulation - Djafari, Jamila; Fernández-Lodeiro, Carlos; Fernández-Lodeiro, Adrián; Silva, Vanessa; Poeta, Patrícia; Igrejas, Gilberto; Lodeiro, Carlos; Capelo, José Luis; Fernández-Lodeiro, Javier (Frontiers in Chemistry, 2019)
In the present work, the synthesis and characterization of silver triangular nanoplates (AgNTs) and their silica coating composites are reported. Engineering control on the surface coating has demonstrated the possibility to modulate the antibacterial effect. Several AgNT-coated nanomaterials, such as PVP (Polyvinylpyrrolidone) and MHA (16-mercaptohexadecanoic acid) as a stable organic coating system as well as uniform silica coating (≈5 nm) of AgNTs, have been prepared and fully characterized. The antibacterial properties of the systems reported, organic (MHA) and inorganic (amine and carboxylic terminated SiO2) coating nanocomposites, have been tested on Gram-positive and Gram-negative bacteria strains. We observed that the AgNTs' organic coating improved antimicrobial properties when compared to other spherical silver colloids found in the literature. We have also found that thick inorganic silica coating decreases the antimicrobial effect, but does not cancel it. In addition, the effect of surface charge in AgNTs@Si seems to play a crucial role toward S. aureus ATCC 25923 bacteria, obtaining MIC/MBC values compared to the AgNTs with an organic coating.